Comparison of Tissue Architectural Changes between Radiofrequency Ablation and Cryospray Ablation in Barrett’s Esophagus Using Endoscopic Three-Dimensional Optical Coherence Tomography - Tsung-Han Tsai; Chao Zhou; Hsiang-Chieh Lee; Yuankai K. Tao; Osman O. Ahsen; Marisa Figueiredo; Desmond C. Adler; Joseph M. Schmitt; Qin Huang; James G. Fujimoto; Hiroshi Mashimo (Gastroenterology Research and Practice)
Two main nonsurgical endoscopic approaches for ablating dysplastic and early cancer lesions in the esophagus have gained popularity, namely, radiofrequency ablation (RFA) and cryospray ablation (CSA). We report a uniquely suited endoscopic and near-microscopic imaging modality, three-dimensional (3D) optical coherence tomography (OCT), to assess and compare the esophagus immediately after RFA and CSA. The maximum depths of architectural changes were measured and compared between the two treatment groups. RFA was observed to induce 230~260 μm depth of architectural changes after each set of ablations over a particular region, while CSA was observed to induce edema-like spongiform changes to ~640 μm depth within the ablated field. The ability to obtain micron-scale depth-resolved images of tissue structural changes following different ablation therapies makes 3D-OCT an ideal tool to assess treatment efficacy. Such information could be potentially used to provide real-time feedback for treatment dosing and to identify regions that need further retreatment.